Switchable quantum anomalous and spin Hall effects in honeycomb magnet EuCd2As2. (1st May 2022) - Li, Bingyang; Sun, Wenli; Zou, Xiaorong; Li, Xinying; Huang, Baibiao; Dai, Ying; Niu, Chengwang
Abstract: Creating and engineering the topological features of intrinsic magnets are essential for topological spintronic applications. Here, we propose a material platform to realize the switchable topological phase transition between quantum anomalous Hall (QAH) and quantum spin Hall (QSH) effects, unlike generally used magnetic doping, by strain engineering. At equilibrium lattice parameters, the QAH effect emerges in EuCd2 As2 quintuple layers with nonzero Chern number and chiral edge states. Accompanying a strain-engineered magnetic phase transition from out-of-plane ferromagnetic (FM) to in-plane antiferromagnetic (AFM) states, a topological phase transition is simultaneously achieved, resulting in the QSH effect, which is explicitly confirmed by nonzero spin Chern number and the emergence of gapless edge states, even without time-reversal symmetry. Remarkably, the obtained QSH effect is highly robust against the magnetic configurations, including FM and AFM configurations with both out-of-plane and in-plane directions, hereby promoting EuCd2 As2 as a wonderful candidate for understanding and utilizing the magnetic topological states in spintronics.